(untitled) (Academia Science Repository, 2023)
Synonymous connections and relationships are found in various areas of the language: in vocabulary, phraseology, morphology and syntax. The synonymy of linguistic units is based on the principle of dialectical unity of the commun and the different, which reflects of the same phenomena or relations of objective reality. From a philosophical point of view, the problem of synonymy is part of a broader problem of identity and difference.